Risk factors for development of pressure ulcers in an intensive care unit - Wouters Franco Rockenbach, Carla (2012)
Introduction: Pressure Ulcers (PU) represent a public health problem, requiring a larger investigation into the incidence and prevalence. Objective: To evaluate the risk factors for the development of PU in patients admitted to ICU. Method: Cross-sectional study that evaluated the risk factors for the development of PU in patients admitted to the ICU and Semi-Intensive at a hospital in northern RS was carried out. Ninety seven individuals participated in this study, and identifying data, use and duration of mechanical ventilation, demographics, comorbidities, characteristics and location of the PU were collected. Results: The most frequent was PU in the region of 39 heels (63.1%). Of the 108 occurrences of PU, 36 (37.1%) individuals were 55 grade I ulcers. A higher incidence of PU in relation to age, length of stay and mechanical ventilation and lower scores on the scale of Glasgow was observed. Conclusion: The incidence of PU was significantly associated with age, sepsis, length of stay and mechanical ventilation and Glasgow scale.